Extensive omental-to-adnexal venous collateralization in a patient with history of tetralogy of Fallot and vena cava inferior agenesis: a case report - Debbaut, Tuur; Abasbassi, Mohamed; Crem, Anne-Sofie De; Depuydt, Sofie; Geers, Joachim; Schepers, Stijn; Olivier, Frederick (International Surgery Journal, 2025)
Tetralogy of Fallot (ToF) is a complex congenital cardiac anomaly increasingly associated with long-term extracardiac vascular adaptations. While arterial collaterals in ToF, such as major aortopulmonary collateral arteries, are well documented, venous collateral pathways remain underreported. Congenital agenesis of the inferior vena cava (IVC), a rare anomaly with a prevalence of 0.0005–1%, typically results in extensive venous collateralization through the azygos, gonadal, and retroperitoneal systems. Omental collateralization, however, has not been described in this context. Herein this report presents a 34-year-old woman with surgically repaired ToF who underwent laparoscopic appendectomy for acute appendicitis. Intraoperatively, extensive dilated venous collaterals were observed coursing from the omentum toward both adnexa. The ovaries appeared enlarged with multiple cystic nodules. Postoperatively, persistent pelvic pain prompted further evaluation. Contrast-enhanced computed tomography (CT) revealed congenital agenesis of the infrarenal IVC with collateral drainage via parauterine and omental venous plexuses. The left ovary demonstrated multiple cystic lesions up to 4.2 cm, consistent with chronic venous congestion rather than acute gynecologic pathology. Transvaginal ultrasound confirmed resolving cystic changes and varicose parauterine and omental plexuses. This case illustrates a previously undescribed omental–ovarian collateral circuit in the setting of IVC agenesis, coinciding with repaired ToF. The anomaly likely contributed to chronic pelvic pain and polycystic ovarian morphology, underscoring the clinical significance of venous remodeling in congenital vascular disease. Recognition of such variants is critical, as they may mimic pelvic masses on imaging and complicate surgery through increased bleeding risk. Awareness of rare collateral pathways expands the spectrum of venous adaptations and highlights implications for surgical, radiological, and reproductive management.